2015
DOI: 10.5194/bg-12-147-2015
|View full text |Cite
|
Sign up to set email alerts
|

The effects of river inflow and retention time on the spatial heterogeneity of chlorophyll and water–air CO<sub>2</sub> fluxes in a tropical hydropower reservoir

Abstract: Abstract. Abundant research has been devoted to understanding the complexity of the biogeochemical and physical processes that are responsible for greenhouse gas (GHG) emissions from hydropower reservoirs. These systems may have spatially complex and heterogeneous GHG emissions due to flooded biomass, river inflows, primary production and dam operation. In this study, we investigated the relationships between the water-air CO 2 fluxes and the phytoplanktonic biomass in the Funil Reservoir, which is an old, str… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
66
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 66 publications
(72 citation statements)
references
References 64 publications
(77 reference statements)
6
66
0
Order By: Relevance
“…As few studies have assessed the variability and the key drivers for pCO 2aq and CO 2 fluxes from lakes integrating spatiotemporal variability, there is a great risk that present assessments are biased. For example, previous intensive pCO 2aq measurements were typically designed to either cover large space under a short time (gas equilibrator screening or manual samples in several points [e.g., Borges et al, 2014;Pacheco et al, 2015;Roland et al, 2010]) or long time in specific locations (sensors collecting data or calculated pCO 2aq from one or a few points over time [e.g., Åberg et al, 2010;Huotari et al, 2009;Pacheco et al, 2015]). Therefore, studies including both spatial and temporal variabilities are needed to better understand variability and to develop representative approaches for large-scale assessments of lake CO 2 fluxes.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…As few studies have assessed the variability and the key drivers for pCO 2aq and CO 2 fluxes from lakes integrating spatiotemporal variability, there is a great risk that present assessments are biased. For example, previous intensive pCO 2aq measurements were typically designed to either cover large space under a short time (gas equilibrator screening or manual samples in several points [e.g., Borges et al, 2014;Pacheco et al, 2015;Roland et al, 2010]) or long time in specific locations (sensors collecting data or calculated pCO 2aq from one or a few points over time [e.g., Åberg et al, 2010;Huotari et al, 2009;Pacheco et al, 2015]). Therefore, studies including both spatial and temporal variabilities are needed to better understand variability and to develop representative approaches for large-scale assessments of lake CO 2 fluxes.…”
Section: Introductionmentioning
confidence: 99%
“…While previous studies over short time periods (1 to 6 h) observed gas transfer velocity (k) to be more variable than pCO 2aq , our work shows that over longer time (days to weeks) pCO 2aq variability was greater and affected CO 2 fluxes much more than k. We demonstrate that ≥8 measurement days distributed over multiple seasons in combination with sufficient spatial coverage (≥8 locations during stratification periods and 5 or less in spring and autumn) are a key for representative yearly whole lake flux estimates. This study illustrates the importance of considering spatiotemporal variability in pCO 2aq and CO 2 fluxes to generate representative whole lake estimates.Spatial variability in pCO 2aq and CO 2 fluxes are now increasingly addressed, e.g., in tropical and boreal reservoirs [Pacheco et al, 2015;Roland et al, 2010;Teodoru et al, 2011] and Amazon floodplain lakes [Rudorff et al, 2011], and have been linked to river inputs, littoral zones, and photosynthesis. The variability of k with fetch or NATCHIMUTHU ET AL.SPATIOTEMPORAL VARIABILITY OF LAKE CO 2 30 PUBLICATIONS…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on greenhouse gases emissions from manmade reservoirs began in the 1990s after the publication of Kelly et al [14], followed by other research [12,13,[18][19][20], and went on to analyze the spatial variations in reservoirs, the sources of organic matter and the processes involved [1,5,10,15,21,24,25].…”
Section: Introductionmentioning
confidence: 99%
“…However, considerable variation exists in the relationship between land use and watershed nutrient export (Puckett 1995;Harding et al 1998;Findlay et al 2001). Therefore, assessing the linkage between LULC and water quality is essential for developing watershed management practices (Uuemaa et al 2005;Wan et al 2014) and controlling land based pollution in rivers, reservoirs (Soares et al 2008;Pacheco et al 2015), and coastal bays (Howarth and Marino 2006).…”
mentioning
confidence: 99%